2020
DOI: 10.1101/2020.02.28.20028514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors related to hepatic injury in patients with corona virus disease 2019

Abstract: Aims:Corona virus disease 2019 has rapidly become the most severe public health issue all over the world. Despite respiratory symptoms, hepatic injury has also been observed in clinical settings. This study aimed to investigate the risk factors involved with hepatic injury in the patients with COVID-19.Methods: A total of 85 hospitalized patients who were diagnosed with COVID-19 in Beijing You'an Hospital were retrospectively analyzed. According to liver function, they were divided into ALT normal group (n=52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 23 publications
6
79
0
5
Order By: Relevance
“…34 Furthermore, few studies reported higher serum pro-inflammatory cytokines and chemokines levels in patients with abnormal liver function compared to those with normal liver function. 16,35 Hence, these data point to a relationship between liver damage and the inflammatory responses induced by SARS-CoV-2 infection. Lastly, some authors suggest that drug-induced liver injury is also a possible contributing factor to laboratory test abnormalities.…”
Section: Covid -19 and Hepati C Inj Urymentioning
confidence: 89%
“…34 Furthermore, few studies reported higher serum pro-inflammatory cytokines and chemokines levels in patients with abnormal liver function compared to those with normal liver function. 16,35 Hence, these data point to a relationship between liver damage and the inflammatory responses induced by SARS-CoV-2 infection. Lastly, some authors suggest that drug-induced liver injury is also a possible contributing factor to laboratory test abnormalities.…”
Section: Covid -19 and Hepati C Inj Urymentioning
confidence: 89%
“…Likewise, published case studies reporting clinical features of patients with COVID-19 have shown that they may develop different degrees of liver dysfunction (summarized in Table 1). In these studies, the incidence of liver injury ranged from 14.8% to 78%, mainly presenting with abnormal levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) accompanied by slightly elevated bilirubin levels [8][9][10][11][12][13][14][15][16][17][18][19]. A deeper look at available data shows higher rates of abnormal levels in severe COVID-19, as high as 78% in one study [18].…”
Section: Covid-19 and The Livermentioning
confidence: 99%
“…Thus, the typical lymphopenia during SARS-CoV-2 infection may result in increases in interleukin-6 (IL-6), IL-10, IL-2 and IFN-c levels and aggravated inflammatory responses, leading not only to pulmonary injury, but also the injury of non-pulmonary organs including the liver [28]. A study of the risk factors involved with hepatic injury in patients with COVID-19, found that lymphopenia and CRP level were independently associated with liver injury, suggesting that inflammatory cytokine storm might be the major mechanism [29].…”
Section: Covid-19 and The Livermentioning
confidence: 99%
“…Since fecal-oral transmission cannot be excluded to date, experts encourage laparoscopic techniques (46), prioritizing non-surgical and interventional management such as stent placement for gastro-intestinal obstruction, avoiding endoscopic procedures (51)(52)(53), providing isolation areas for invasive interventions for suspected or confirmed cases (51,53). As for the medical management, a group of experts suggested maintaining chemotherapy for metastatic patients, providing necessary treatment for patients who have a progressive disease and decreasing intensity and frequency of adjuvant chemotherapy (54). Chinese physicians adopted modifications not only in the therapeutic strategies but also in the diagnostic procedures of cancer patients (55,56).…”
Section: The Chinese Experiencementioning
confidence: 99%